Analisis Perbandingan Ekonomis Penggunaan Penerangan Jalan Umum Solar Cell dengan Penerangan Jalan Umum Konvensional di Bandar Udara Djalaluddin Gorontalo - Bunahri, Rifqi Raza (SKY EAST: Education of Aviation Science and Technology, 2023)
This study aims to conduct an economic comparison analysis between the use of solar cell street lighting and conventional street lighting at Djalaluddin Airport in Gorontalo. The research method employed is quantitative, with data collection through observation, interviews, and document analysis. The findings indicate that the utilization of solar cell street lighting at UPBU Djalaluddin Airport is relatively ineffective from an economic standpoint. The operational costs for battery replacement in solar cell street lighting are comparatively higher than using PLN electricity in conventional street lighting. Furthermore, the initial investment cost for solar cell street lighting is significantly more expensive than conventional street lighting. The total costs of solar cell street lighting over a 10-year period are also higher compared to conventional street lighting. However, the operational costs for solar cell street lighting are simpler, limited to the expenses for cleaning the solar panels, while the operational costs for conventional street lighting depend on the government-regulated Basic Electricity Tariff (TDL).